2017
DOI: 10.1103/physrevd.96.125006
|View full text |Cite
|
Sign up to set email alerts
|

Spinning gravitating Skyrmions in a generalized Einstein-Skyrme model

Abstract: We investigate properties of self-gravitating isorotating Skyrmions in the generalized Einstein-Skyrme model with higher-derivative terms in the matter field sector.These stationary solutions are axially symmetric, regular and asymptotically flat.We provide a detailed account of the branch structure of the spinning solutions in the topological sector of degree one. We show that additional branches of solutions appear, as the angular frequency increases above some critical value, these "cloudy" configurations c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The O(3) scalar field ansatz compatible with stationarity and axial symmetry needs not to be t, ϕ independent. The solutions in this work are found within an ansatz 2 inspired by previous work done for an O(4) Skyrme model [49,51,50,52,53,54], with:…”
Section: Ansatzmentioning
confidence: 99%
“…The O(3) scalar field ansatz compatible with stationarity and axial symmetry needs not to be t, ϕ independent. The solutions in this work are found within an ansatz 2 inspired by previous work done for an O(4) Skyrme model [49,51,50,52,53,54], with:…”
Section: Ansatzmentioning
confidence: 99%
“…As found in [20], however, the flat spacetime Skyrmions possess axially symmetric spinning generalizations 1 , which may, moreover, gravitate [21] (see also [22]). The existence of spinning Skyrmions raises the question if four dimensional asymptotically flat spinning BHs with Skyrme hair exist.…”
Section: Introductionmentioning
confidence: 92%
“…[40]. Spinning gravitating Skyrmions were considered [42,43] and it was further found that the BPS-Skyrme model does not possess spinning Skyrmions [43] -neither in a curved nor in a flat background. More exotic configurations like the gravitating axisymmetric sphalerons in the Einstein-Skyrme model have also been studied [44].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, since neutron stars are expected to possess some amount of spin, which is acquired during a star's core collapse, the BPS-Skyrme model cannot quite be a good approximation due to the instability found in Ref. [43]. In some limit it may give reasonable answers, nevertheless.…”
Section: Introductionmentioning
confidence: 99%